2022
DOI: 10.1108/ijmpb-02-2022-0035
|View full text |Cite
|
Sign up to set email alerts
|

Improved reliability in planning large-scale infrastructure project delivery through Alliancing

Abstract: PurposePrice reliability for complex and highly complicated infrastructure projects is problematic. Traditional project delivery approaches generally fail in achieving targeted end cost reliability. However, integrated project delivery (and particularly Alliancing), develop a far more reliable and robust project delivery plan and outturn time-cost targets. This paper aims to explore why this may be the case.Design/methodology/approachThis case study investigated the project design, planning, cost/time estimati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…Sanchez-Silva [29] examined the advantages of introducing flexibility in design and construction using airport design and extension as an example. Walker et al [30] developed a delivery strategy for a complicated project using an infrastructure project in Australia as an example to optimize cooperation. In a case study in Amsterdam, the Netherlands, Rosok et al [31] found that collaborative decision making in XFN projects has additional complexity and requires the governance of uncertainty.…”
Section: Introductionmentioning
confidence: 99%
“…Sanchez-Silva [29] examined the advantages of introducing flexibility in design and construction using airport design and extension as an example. Walker et al [30] developed a delivery strategy for a complicated project using an infrastructure project in Australia as an example to optimize cooperation. In a case study in Amsterdam, the Netherlands, Rosok et al [31] found that collaborative decision making in XFN projects has additional complexity and requires the governance of uncertainty.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, Love and Ika [84] and Love et al [94] show that cost overruns do not vary between non-BIM and BIM-enabled projects. Further, with the increasing use of Alliances and Two-Stage Management Contracting, we have seen projects procured using these delivery methods less susceptible to cost overruns [51], [84]. Indeed, a collaborative team that jointly prepares the target outturn cost estimate and works collectively to meet it often helps improve a project's cost performance.…”
Section: Stagnation: Generally the Same Results But A Different Eramentioning
confidence: 99%
“…Worldwide, governments sought ways to improve the delivery of their capital assets and, in so doing, initiated reforms to their policies and practices as a consequence [39][40][41][42][43][44][45][46]. As part of these larger analyses, scope and design changes, the form of procurement method (i.e., separation of design and construction activities), poor project management, ineffective project teams, and the economic, institutional, and political environment have been repeatedly identified as key contributors to cost overruns [6], [17], [27], [47][48][49][50][51]. Let us briefly consider each of these issues in turn.…”
Section: B the Procurement And Management Of The Projectmentioning
confidence: 99%
See 1 more Smart Citation
“…In the three most relevant project studies journals (IJPM, PMJ, IJMPB), only two papers focused on Design Thinking in the context of projects have been published (Ben Mahmoud-Jouini et al, 2016;Hölzle & Rhinow, 2019). Another (Walker et al, 2022) shows that design thinking can shape collaborative behaviours and project governance. The central idea of this essay is that Design Thinking has much more to offer to projects, project scholars and project practitioners both from a phenomenological perspective (i.e., the planning and delivering of projects, particularly complex projects) and a field of study perspective (i.e., the studying of projects by project scholars).…”
Section: Moving Forwardmentioning
confidence: 99%